Construction of a novel asymmetric imidazole-cored AIE probe for ratiometric imaging of endogenous leucine aminopeptidase. Issue 54 (11th June 2021) - Huang, Xueyan; Lei, Qian; Huang, Shuai; Zeng, Hongliang; Feng, Bin; Zeng, Qinghai; Hu, Yibo; Zeng, Wenbin
Abstract : A novel asymmetric tetraarylimidazole-based AIE probe for ratiometric imaging of endogenous LAP. Abstract : We report a rational strategy to deliberately construct the first asymmetric tetraarylimidazole-based AIE probe, integrating AIE behavior in synergy with ESIPT character to image endogenous LAP for the first time. It offered good sensitivity and selectivity, and concomitantly, was applied successfully for real-time tracking of LAP in the cisplatin-induced liver injury zebrafish model.